Analisis Keberadaan Rambu-Marka terhadap Kepatuhan Pengendara pada Simpang (Studi Kasus : Jalan Pasar Tua Kabupaten Banggai Laut Provinsi Sulawesi Tengah) - Hamid, Sri Megawati Putri; Maryam, St Maryam; Syarkawi, Mukhtar Thahir (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Many drivers do not comply with the existence of signs which results in various traffic problems, therefore there is a need to find a way to solve these problems. The formulation of the problem is what facilities are available, what factors influence driver compliance with the presence of marking facilities and efforts that can be made to increase driver compliance. This research aims to analyze the completeness of existing facilities, and factors that influence driver compliance with signage facilities and formulate efforts to improve compliance. The population is all drivers at the research location, with a sample of 385 respondents. The analytical method used is Multiple Linear Regression with SPSS. The results of the analysis showed that the completeness of the road facilities was still inadequate and incomplete. Influence of knowledge (X1): 6.7%; self-awareness (X2): 33.7%; mental and behavioral (X3): 38.4% and law enforcement efforts (X4): 27.7%. Efforts are made to increase compliance with preventive and represent tive measures.